2021
DOI: 10.2196/25731
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality–Based Psychotherapy in Social Anxiety Disorder: fMRI Study Using a Self-Referential Task

Abstract: Background Although it has been well demonstrated that the efficacy of virtual reality therapy for social anxiety disorder is comparable to that of traditional cognitive behavioral therapy, little is known about the effect of virtual reality on pathological self-referential processes in individuals with social anxiety disorder. Objective We aimed to determine changes in self-referential processing and their neural mechanisms following virtual reality tr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 57 publications
1
16
0
Order By: Relevance
“…The inclusion criteria for the SAD group were set as follows: (1) men and women aged between 19 and 31 years using the Korean language; (2) condition meeting the Diagnostic and Statistical Manual of Mental Disorders, fourth edition (DSM-IV) criteria for SAD, as evaluated by the Mini-International Neuropsychiatric Interview [ 17 ]; (3) no psychiatric comorbidity, except for depression and panic disorder, and no experience in psychotropic drug treatment; (4) not currently receiving psychotherapy; (5) not currently diagnosed with medical or neurological disorders; (6) no history of psychotic symptoms that can be triggered by VR interventions; and (7) no susceptibility to visual stimuli. We set the exclusion criteria as follows: (1) any history of organic brain damage or intellectual disability; (2) a history of psychotic symptoms that can be triggered by VR interventions; (3) vulnerability to visual stimuli; and (4) ineligibility for participation in a magnetic resonance imaging assessment (during the study, we performed a functional magnetic resonance imaging evaluation for another project in the same subjects) [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…The inclusion criteria for the SAD group were set as follows: (1) men and women aged between 19 and 31 years using the Korean language; (2) condition meeting the Diagnostic and Statistical Manual of Mental Disorders, fourth edition (DSM-IV) criteria for SAD, as evaluated by the Mini-International Neuropsychiatric Interview [ 17 ]; (3) no psychiatric comorbidity, except for depression and panic disorder, and no experience in psychotropic drug treatment; (4) not currently receiving psychotherapy; (5) not currently diagnosed with medical or neurological disorders; (6) no history of psychotic symptoms that can be triggered by VR interventions; and (7) no susceptibility to visual stimuli. We set the exclusion criteria as follows: (1) any history of organic brain damage or intellectual disability; (2) a history of psychotic symptoms that can be triggered by VR interventions; (3) vulnerability to visual stimuli; and (4) ineligibility for participation in a magnetic resonance imaging assessment (during the study, we performed a functional magnetic resonance imaging evaluation for another project in the same subjects) [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…Third, several studies investigating VRET for social anxiety were not included in the review as they were outside of the scoping criteria. Some of these expand on innovative techniques such as cloud-based VRET (113), or broaden our understanding of VRET effectiveness by using functional magnetic resonance imaging (114), yet the cumulative effects of such protocols are still unknown due to their recency. Finally, this review focused on adults due to differences in developmental trajectories of social anxiety as well as limited availability of protocols for children and adolescents.…”
Section: Review Limitationsmentioning
confidence: 99%
“…Cabeza et al [8] linked the contribution of emotion and vividness of AM to the amygdala, and visual cortex of the brain respectively. Hur et al 's fMRI study reported enhanced cognitive and physiological processing in people with social anxiety order through a VR-based exposure therapy where they were asked to report if the emotional words shown to them were self-relevant [29]. Even though fMRI provides a deeper understanding of AM recall process but due to non-mobile, large and complex setup, it becomes challenging to use it for mobile and interactive VR applications.…”
Section: Emotional Autobiographical Memory and Physiological Signalsmentioning
confidence: 99%